Enhancement of the Command-Line Environment for use in the Introductory Statistics Course and Beyond. Issue 3 (2nd September 2021) - Gerbing, David W.
ABSTRACT: R and Python are commonly used software languages for data analytics. Using these languages as the course software for the introductory course gives students practical skills for applying statistical concepts to data analysis. However, the reliance upon the command line is perceived by the typical nontechnical introductory student as sufficiently esoteric that its use detracts from the teaching of statistical concepts and data analysis. An R package was developed based on the successive feedback of hundreds of introductory statistics students over multiple years to provide a set of functions that apply basic statistical principles with command-line R. The package offers gentler error checking and many visualizations and analytics, successfully serving as the course software for teaching and homework. This software includes pedagogical functions, data analytic functions for a variety of analyses, and the foundation for access to the entire R ecosystem and, by extension, any command-line environment.